EVALUASI REVITALISASI PASAR TRADISIONAL BERBASIS KEMITRAAN, STUDI KASUS: PASAR TRADISIONAL BANDARJO KABUPATEN SEMARANG - Bunga Wina Alvina; Priyatno Harsasto (Journal of Politic and Government Studies, 2020)
The situation in the era of global competition have cornered the existence oftraditional markets where the presence of modern markets has increased and become thepeople's choice to shop because it is considered more comfortable and cleaner. Therefore, thepolicy of traditional market revitalisation is a big push for the local government to maintainthe existence of traditional markets. In 2017-2018, the government of Semarang Regency hasrevitalised the traditional market of Bandarjo because the existence of Bandarjo Plazabuilding was considered to be old and not yet functioned optimally. This study discusses howto revitalise the traditional market of Bandarjo, and the process of implementing partnershipsas a means of revitalising the traditional market of Bandarjo. This type of research useddescriptive qualitative data collection technique in the form of interviews, observation anddocumentation. The data obtained is then carried out the process of qualitative data analysisby data reduction, data presentation and conclusions. The result of this study is the collaboration between Disperindag (Department ofIndustry and Commerce) and Persada started after the revitalisation planning stages, whichare the implementation and management stage. During the revitalisation stage, Persadacooperated with Disperindag in the socialisation related to the development schedule,relocation, and supervision. After revitalisation, Persada was given the authority to managegovernment assets in the form of MCK (Bathing, Washing and Toilet) and parking.Partnership in the stage of implementation and management between Persada and theDepartment of Industry and Commerce, does not have equality with the principle ofpartnership. The absence of SOP (Standard Operating Procedure) or the standard of marketcleanliness results in different perceptions where market cleanliness and MCK according tomarket visitors are not clean enough while Persada considers it is clean. The conclusion of this study is that the partnership between Disperindag and Persadacannot be said to be productive because the role of Disperindag looks more dominant thanPersada in managing the traditional market of Bandarjo. Based on these conclusions, thesuggestion that can be given is that the partnership between Disperindag and Persada isexpected to be continued and to be accompanied by improving management of the traditionalmarket of Bandarjo through the creation of SOP (Standard Operating Procedure), especiallyfor market cleanliness and MCK (Bathing, Washing, Toilet) issues. Keywords: Process Evaluation, Partnership, Traditional Market Revitalisation,Management